Beat Phenomenon Analysis of Concrete Beam with Piezoelectric Sensors. (23rd September 2012) - Li, Xu; Huo, Linsheng; Li, Hongnan
Abstract : The focus of this paper is to give a better understanding of beat phenomenon in the free vibration test of a concrete beam with piezoelectric ceramic sensors from the view of mathematics. The cause of beat phenomenon from piezoelectric ceramic sensors embedded in the concrete beam is illustrated and the influence factors of beat phenomenon are discussed. The results show that the beat phenomenon from piezoelectric ceramic sensors in the concrete beam is caused by the coupled responses with similar model frequencies in different directions. The influence factors of beat phenomenon due to damping effect, impact direction, sensor position and sectional dimension are discussed. As the damping ratios increased, the amplitude of beat signal will die out in an exponential decay. Meanwhile, the damping has a tiny influence on the beat frequency of system response, the amplitudes of beat signal both in the time and frequency domain are changed with the variation of impact direction. In addition, the amplitude of beat signal will be also changed with the position of sensors altered. The beat frequency will get more with the greater difference of sectional dimension.